Mesenchymal Stromal Cell Dependent Regression of Pulmonary Metastasis from Ewing’s - Hayes-Jordan, Andrea; Wang, Yong Xin; Walker, Peter; Cox, Charles S. (Frontiers in Pediatrics, 2014)
Introduction: Ewing’s sarcoma (ES) is the second most common bone tumor in children. Survival has not improved over the last decade and once pulmonary metastatic disease is present, survival is dismal. Mesenchymal stromal cell (MSC) therapy has shown potential benefit for Kaposi's sarcoma; however, the role of progenitor cell therapies for cancer remains controversial. MSC treatment of ES or pulmonary metastatic disease has not been demonstrated. We have developed an orthotopic xenograft model of ES in which animals develop spontaneous pulmonary metastases. Within this model, we demonstrate the use of MSCs to target ES lung metastasis. Materials and Methods Human ES cells were transfected with luciferase and injected into the rib of nude mice. Development of pulmonary metastases was confirmed by imaging. After flow cytometry based characterization, MSC’s were injected into the tail vein of nude mice with established local ES tumor or pulmonary metastasis. Mice were treated with intravenous MSCs weekly followed by bioluminescent imaging. Results The intravenous injection of MSCs in an ES model decreases the volume of pulmonary metastatic lesions; however, no effect on primary chest wall tumor size is observed. Thus verifying the MSC preferential homing to the lung. MSCs are found to ‘home to’ the pulmonary parenchyma and remain engrafted up to 5 days after delivery. Discussion MSC treatment of ES slows growth of pulmonary metastasis. MSC’s have more affinity for pulmonary metastasis and can effect a greater decrease in tumor growth in the lungs compared to the primary tumor site